Management of Plastıc Bronchıtıs in Chıldren: A Case Report and Lıterature Revıew - Volkan Sarper Erikci (Journal of Preventive Medicine And Care, 2020)
Plastic bronchitis (PB) is a rare disease characterized by the presence of mucofibrinous plugs which may occlude and conform the shape of tracheobronchial tree. These casts are exteremely cohesive. Most common presenting symptoms include cough, fever and dyspnea and if the cohesive casts occlude the airway totally life-threatening complications and even death may occur. The aim of treatment is to remove the casts and adress the symptoms. In this study a 6-year-old boy with PB is presented. In addition to medical treatment obstructing casts were removed via rigid bronchoscope. It is aimed to review the clinical and radiographic features and choices of treatment in this disease.
Keywords: Plastic bronchitis